2012
DOI: 10.1590/s0004-282x2012000600007
|View full text |Cite
|
Sign up to set email alerts
|

Motor assessment in patients with Duchenne muscular dystrophy

Abstract: OBJECTIVE: Evaluate muscle force and motor function in patients with Duchenne muscular dystrophy (DMD) in a period of six months. METHOD: Twenty children and adolescents with diagnosis of DMD were evaluated trough: measurement of the strength of the flexors and extensors of the shoulder, elbow, wrist, knee and ankle through the Medical Research Council (MRC), and application of the Motor Function Measure (MFM). The patients were evaluated twice within a six-month interval. RESULTS: Loss of muscle strength was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
8
1
5
Order By: Relevance
“…Moreover, the present study found stronger relationships between muscle strength and MFM than previous studies 13, 15,18,19 . This fact can be attributed to the extensive practice with patients with DMD of all the examiners that participated in this study.…”
Section: Bartels Et Alcontrasting
confidence: 76%
See 3 more Smart Citations
“…Moreover, the present study found stronger relationships between muscle strength and MFM than previous studies 13, 15,18,19 . This fact can be attributed to the extensive practice with patients with DMD of all the examiners that participated in this study.…”
Section: Bartels Et Alcontrasting
confidence: 76%
“…In 2012, Diniz et al 19 investigated the muscle strength and motor function of 20 patients with DMD. They found moderate to strong correlations between MRC scores and all Dimensions of MFM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Some medical teams begin corticosteroid treatment even sooner, between 2 years and 4 years of age, with encouraging results. MFM validity was also established in DMD corticosteroids-naive patients, [16][17][18] as well as in a small number of corticosteroids-treated patients for a short duration of follow-up (<2y). 8 Clinical trials in neuromuscular diseases require a rigorous approach to monitor longitudinal changes in neuromuscular status over time.…”
mentioning
confidence: 99%